Using Cooperative Learning Methods (STAD and Think Pair and Share) to improve the Students’ Reading Comprehension - Marudut Sitorus; Pamela Harvey (Universitas PGRI Madiun, 2020)
This research aimed to investigate the effectiveness of using cooperative learning methods in developing the students’ reading ability in English class and their attitudes toward cooperative learning. The research focused on the students’ interest to study English by working in groups and how their academic achievement increased. The research was conducted in a Christian school in Kalimantan. The data was obtained by giving students a questionnaire, reading test and observation of the application of STAD (Student Team Achievement Division) and Think Pair and Share cooperative methods in the two cycles. The STAD cooperative method was applied in the first cycle; and Think pair and Share was applied in the second cycle. After collecting and analyzing the data, the researcher noted that these two cooperative methods helped to develop the students’ reading skills because they helped understand the story and the vocabulary. The questionnaire given to the students also showed that the majority of the students liked to learn through cooperative learning activity because they liked to share their ideas.